The formation of future teachers professional readyness to innovation activity by means of digital technologies (Revista de Investigaciones Universidad del Quindío, 2022)
The training of future specialists for innovation activity is a leading trend of modern higher pedagogical education, which is due to the integration of Ukraine into the European educational space. The article actualizes the problem of future teachers’ professional readiness formation for innovation activity using digital technologies. General science, synthesis, comparison, analysis, generalization and systematization of studies of domestic and foreign scientists are employed. Based on the results, the essence of the concept “professional preparedness of future teachers for innovation” has been revealed. It has been found that the professional readiness of future teachers for innovation is the outcome of integrative personal education, and professional training, featured via a blend of cognitive (knowledge regarding the concept of the innovation and profession), motivational (incentives for interests and innovation), reflexive (capability of analyzing results), innovative activity and praxeological (innovation competence actualization) elements that permit conducting professional tasks of innovative nature. It has been concluded that a modern teacher can’t conduct educational actions with no utilizing advanced digital technologies, and the education informatization comprises enhancing the future teachers’ training in the information educational environment of higher education institutions.
Keywords: informatization of education; future teachers; digital technologies; digital competence; professional training